Third Five-Year Plan A Draft Outline Volume II (Supplementary) Government of Uttar Pradesh, Planning Department - Planning Commission (Planning Commission, 1960)
Since forwarding the Draft Plan the State had the benefit of the views of some Central Ministries regarding certain important sectors, proposals in respect of which have been somewhat modified. The modifications under Minor Irrigation, Co-operation, Forests and Food Processing Industries fall in this category. Also on a further study of the National Plan for Transport and Communications, it appeared that in the Third Plan few additional areas in the State will be opened up by the Railways and the major part of the Railway programme in this State will be confined to completion of projects already in hand and to improvement of operational efficiency on the existing railway lines. In view of the backwardness of the State in roads, needs of the backward pockets, and the demand on the road transport sector for supporting a production programme as envisaged in the State Plan, the Road Development programme had to be revised from Rs.28 crores to Rs.37 crores.
Government of Uttar Pradesh Planning Department